ANALISIS KEMANDIRIAN DAN EFEKTIVITAS KEUANGAN DAERAH PADA KABUPATEN/KOTA DI PROVINSI ACEH - Soviana, Amelia; Suparno, Suparno (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study was aimed to analyze the financial performance of regencies government in Aceh Province in 2014-2019 based on the ratio of independently and the ratio of regional financial effectiveness. This research is quantitative descriptive. The data used is secondary data in the form of a budget realization report (LRA). The results showed: 1) The independently of regencies government in Aceh Province in 2014-2019 fluctuates every year with an average of 10.33% falling into the very low category with an instructive relationship pattern, namely the central government still plays a more dominant role than the regions. 2) The trend of independently of regencies government in Aceh Province in 2014-2019 an average of 95.62% shows that there is no development. 3) The financial effectiveness of regencies government in Aceh Province in 2014-2019 tended to decline each year by an average of 92.64%, based on the category of financial capacity, it was said to be quite effective. 4) The trend of regencies government in Aceh Province in 2014-2019 an average of 94.20% shows no progress.